THE DEHUMANIZATION IN OBJETOS ENAJENADOS (1971) BY YOLANDA WESTPHALEN - Cachay Luna, Christian Bryan (2020)
Regarding the recent publication of Yolanda Westphalen's Obra completa (2018), it is necessary to rediscover her writings, in which constant reflection on the human condition stands out. In particular, in his second book of poems, Objetos Enajenados (1971), the reflection on these objects, be it through critical observation, dialogue or personification, it concludes in a dehumanizing vision. The analyzes were carried out on the basis of the contributions of Stefano Arduini's General Textual Rhetoric and the argumentative techniques according to Perelman and Olbrechts-Tyteca.